Microstructure of Titanium‐Cement‐Lithium Disilicate Interface in CAD‐CAM Dental Implant Crowns: A Three‐Dimensional Profilometric Analysis. (22nd August 2013) - Cresti, Stefano; Itri, Angelo; Rebaudi, Alberto; Diaspro, Alberto; Salerno, Marco
Abstract: Background: Peri‐implantitis is an infection of the implant surface caused by adhesion of bacteria that generate bone resorption and sometimes even consequent implant loss. Both screw‐retained and cemented fixed implants are affected. Purpose: The purpose of this study is to investigate the morphological defects at the cemented interface between titanium abutment and ceramic crown, comparing different adhesive cements used to fill the marginal gap. Materials and Methods: Twelve computer‐aided design–computer‐aided manufacturing dental crowns were cemented to titanium abutments using three different resin composite cements. Sealed margins were polished using grommets with descending diamond particle size. Three groups of four crowns each were made according to the cement used, namely RelyX Unicem (3 M ESPE), Panavia F 2.0 (Kuraray), and NX3 (Nexus Kerr). Samples were analyzed using optical inspection, three‐dimensional profilometry, and image analysis, including analysis of variance. Results: Although RelyX showed significantly lower root mean square surface roughness (4.4 ± 1.5 μm) than that of NX3 (7.0 ± 2.9 μm), it showed no significant difference with Panavia (3.7 ± 1.5 μm). The marginal gap was significantly wider in Panavia (149 ± 108 μm) as compared with NX3 (71 ± 45 μm) and Relyx (64 ± 34 μm). For all groups, homogeneous heights of both metal‐cement and ceramic‐cement gaps were observed. Moreover, all samples showed homogeneity of the margins and absence of instrumental bias, thus validating both procedure and materials. Conclusions: When using the chosen polishing method, RelyX Unicem showed both low roughness and marginal width, and thus the smoothest and more continuous abutment‐crown interlayer, promising a low probability of occurrence of peri‐implantitis.